PESANTREN DALAM POLITIK DAN KEBIJAKAN PENDIDIKAN DI INDONESIA - Kharisul Wathoni (IAIN Ponorogo, 2020)
A political policy that is carried out within a certain period of time seems to encourage the development of a social system as an effort to maintain the security of the system and political policies. As the government policy given to pesantren as Islamic educational institutions in Indonesia, has had an impact on the development of Islamic education institutions in Indonesia from basic education institutions and even to the formation of higher education institutions that are able to compete with general education institutions. There are 5 characteristics inherent in Islamic boarding schools, namely: pondok, mosque, teaching of classical Islamic books, santri, and kyai. Islamic boarding schools in Indonesia have a very big role, both for the progress of Islam itself and for the Indonesian nation as a whole. Based on existing records, religious education activities in the archipelago have been started since 1596. These religious activities are later known as Islamic boarding schools. Ulama began to realize that the traditional Islamic boarding schools and education systems were no longer suited to the Indonesian climate at that time. Therefore, an idea emerged about the need to develop and renew Islamic education in Indonesia.